2017
DOI: 10.1111/medu.13334
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the institutional logics of health professions education scholarship units

Abstract: Identifying the configuration of these three logics within and across HPESUs provides insights into the reasons why individual units are structured and function in particular ways. Having a common language in which to discuss these logics can enhance transparency, facilitate evaluation, and help leaders select appropriate indicators of HPESU success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 26 publications
0
36
0
1
Order By: Relevance
“…2 Some institutions have developed academies of medical educators 3 while others have created education scholarship units. 4 Recently, a survey of general internal medicine division directors demonstrated that directors find a wide variety of scholarly work done by clinician educators to be important. 5 Despite these advances, educators often lack the time, 6 resources, skills, or financial support 5,7 to successfully complete scholarly work.…”
Section: -William Oslermentioning
confidence: 99%
“…2 Some institutions have developed academies of medical educators 3 while others have created education scholarship units. 4 Recently, a survey of general internal medicine division directors demonstrated that directors find a wide variety of scholarly work done by clinician educators to be important. 5 Despite these advances, educators often lack the time, 6 resources, skills, or financial support 5,7 to successfully complete scholarly work.…”
Section: -William Oslermentioning
confidence: 99%
“…Health professions education (HPE) has recently witnessed a marked increase in the number of institutional structures developed to support scholarship in the field [1][2][3][4][5][6]. A growing body of research is investigating health professions education scholarship units (HPESUs), defined as organizational structures actively engaged in HPE scholarship [7].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research is investigating health professions education scholarship units (HPESUs), defined as organizational structures actively engaged in HPE scholarship [7]. This research highlights how each HPESU embraces a unique configuration of operational scopes, organizational configurations, and purposeful foci of activities and research [4][5][6][7]. An exploratory study of HPESUs in Canada, Australia, New Zealand, and the USA [5] con-Exploring perspectives on health professions education scholarship units from sub-Saharan Africa structed an understanding of how three institutional logics underpinning HPESUs-that is, the norms and values that are shaped over time and come to characterize an organization-influence the way in which these units function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research investigating how HPE research communities operate in bricks and mortar institutions suggests that specific logics underpin the workings of HPE scholarship units (HPESUs) . One logic that is particularly important (and interpreted in a variety of ways) is the weighting of research, service and teaching mandates within the HPESU . Some HPESUs are primarily research‐oriented, others are primarily service‐oriented, and others endeavour to balance research, service and teaching.…”
mentioning
confidence: 99%